The Impact Of Nusa Data Prima Corner Wifi In Improving Community Economy Based On Maqashid Syari'ah - Sulistyowati Sulistyowati; Achmad Yasin; Achmad Zarkoni (MediaTrend, 2023)
The rapid development of technology has influenced the behavior of human life, including the economic aspect. The current shift in economic transactions is more or less shifting from offline to online so that it affects the economic activities of the community which are also growing and expanding. That is why, nowadays internet access is not only needed in urban areas, but also important for rural communities, especially to improve the economic level of their people. This study examines the Impact of Nusa Data Prima Wifi Corner on Economic Improvement and the Impact of using Nusa Data Prima Wifi Corner on Community Economic Improvement in terms of Maqasid Syariah. The qualitative method in this study was carried out through interviews, then documenting the data found, and making observations in the field. This research resulted in the following conclusions: (1) The impact of the wifi corner is an increase in the economy where residents who previously only relied on income from plantation and agricultural products now have other income, both from online sales and from other business results such as buying and selling stocks and brokers buying and selling cars and others, some residents who become partners in the sale of vouchers also benefit from the sale of these vouchers. (2) Judging from the theory of maqashid syari'ah the impact of the existence of Wifi Corner is a form of benefiting dhoruriyah, hajiyyah and tahsiniyah.